DENSITY OF Pseudomonas sp. BACTERIA AND HETEROTROPHIC BACTERIA IN DUMAI SEAWATER OFRIAU PROVINCE - Masdini, Alvira; Feliatra, Feliatra; Effendi, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Pseudomonas sp. is a hydrocarbonoclasticbacteria that is capable of degrading various types of hydrocarbons. Pseudomonas sp.including bacteria that have the potential to become pathogens. This research was conducted in April to May 2018. This study aims to calculate the density of Pseudomonas sp.bacteriaand heterotrophic bacteria in Dumai sea waters, comparison of the desity of Pseudomonas sp. bacteria to heterotrophic bacteria at each station and the resistance of Pseudomonas sp. to antibiotics. The result showed that densityPseudomonas sp. ranged from 2.25 x 105- 6.08 x 105 CFU/ml. The highest number of Pseudomonas sp.at station 1 and lowest at station 5. The total number of heterotrophic bacteria ranged from 7.37 x 106 - 10.38 x 106 CFU/ml. The highest number of heterotrophic bacteria at station 4 and the lowest at station 5.The highest percentage rasioof density of Pseudomonas sp. bacteri to heterotrophic bacteria was in station 1 (6.26%) and the lowest was in station 4 (2.86%). The results of isolation of bacteria obtained 25 pure isolates and tested for bacterial resistance to antobiotics. Results of isolation bacteria obtained 25 pure isolates and tested the resistance ofPseudomonassp. bacteriato antibiotics.Chloramphenicolantibiotic test results showed 2 isolates classified as sensitive with inhibition zone of 21,3 – 21,9 mm, 1 isolate including resistance with 9,7 mm inhibition zone, with a 22 isolates classified as intermediate with a inhibition zone of 9.7 – 19.6 mm. Two other antibiotics Penicillin and Isoniazid, all bacterial isolates were resistant with the inhibition zone range from 1.2 – 4.6 mm and 1 – 2.8 mm respectively Keyword: Density, Pseuomonas sp.,Heterotrophic Bacteria, Antibiotics